Assimilation of KOMPSAT-5 Bending Angle in GSI 4D-EnVar Assimilation System - Dutta, Suryakanti; Prasad, V. S.; Vandenberghe, François; Shao, Hui; Yoe, James G. (MAUSAM, 2024)
Bending Angle from KOMPSAT-5 (Korea Multi-Purpose Satellite-5) GNSS-RO (Global Navigation Satellite System - Radio Occultation) data is assimilated in Global Data Assimilation and Forecast System. The observations are incorporated using the GSI (Grid-point Statistical Interpolation) 4D-EnVAR analysis scheme. Before assimilation, the data is processed and undergoes quality control by CDAAC (COSMIC Data Analysis and Archive Center), UCAR (University Corporation for Atmospheric Research). The evaluation & assessment procedure goes through four phases: 1) diagnostics through assimilation in cold start mode; cyclic assimilation for a 2) summer and a 3) winter month; 4) a case study for investigating the impact on the severe weather event. Two separate NWP forecast experiments, a control (named CTRL) and the experiment (called KOMPSAT5), are run simultaneously. The only difference between the two is the presence (in KOMPSAT5) and absence (in CTRL) of the KOMPSAT-5 GNSS-RO. Summer cycle statistics show better, significant and consistent improvement compared to the winter cycle.